Horizontal Violence and the Quality and Safety of Patient Care: A Conceptual Model - Christina Purpora; Mary A. Blegen (Nursing Research and Practice)
For many years, nurses in international clinical and academic settings have voiced concern about horizontal violence among nurses and its consequences. However, no known framework exists to guide research on the topic to explain these consequences. This paper presents a conceptual model that was developed from four theories to illustrate how the quality and safety of patient care could be affected by horizontal violence. Research is needed to validate the new model and to gather empirical evidence of the consequences of horizontal violence on which to base recommendations for future research, education, and practice.